Reservoir characteristics and controlling factor of shale gas in Lower Cambrian Niutitang Formation, South China - Pengfei Wang; Zhenxue Jiang; Bo Han; Peng Lv; Can Jin; Kun Zhang; Xin Li; Tingwei Li (Petroleum Research, 2018)
Large-scale exploration and development of shale gas in Lower Cambrian Niutitang Formation of South China has been carried out in recent years, but the result is not good, only except some drilling wells in Jingyan-Qianwei area of Sichuan Basin and Yichang of Hubei obtain some commercial gas flows. In order to clarify reasons for failure of shale gas exploration and development in Niutitang Formation around Sichuan Basin and to provide reservoir geological parameters for subsequent efficient exploration and development, taking a case of shale gas reservoirs in Lower Cambrian Niutitang Formation in northeast Chongqing around Sichuan Basin, some experimental methods, such as analysis of organic carbon pyrolysis, determination of equivalent vitrinite reflectance, focused ion beam scanning electron microscope (FIB-SEM) and other are adopted in this study. The results show that the average TOC of shale samples in Niutitang Formation in northeast Chongqing is 3.1%, the equivalent vitrinite reflectance ranges from 3.0% to 4.0%, and the degree of thermal evolution reaches the post-mature–metamorphic stage. Due to excessively high degree of the thermal evolution, organic pores in shale samples are not developed in Lower Cambrian Niutitang Formation in the study area, instead, micro-nano pores dominated by intergranular pores and intragranular pores are developed in the shale. The degree of the thermal evolution controls the sustaining gas generation of kerogen and retained liquid hydrocarbons in the shale, it also controls the development of organic pores of the shale. The evolution of organic pores and hydrocarbon generation in the shale of Niutitang Formation in northeast Chongqing around Sichuan Basin do not match best with each other, that is, during development period of a large number of organic pores, thermal evolution degree of reservoirs is further enhanced because the strata are not uplifted in time, therefore, the quantity of organic pores is decreased sharply, the shale gas would be escaped due to the absence of organic pores as effective storage space after the shale gas generation. Therefore, the efficient exploration and development of the shale gas in Lower Cambrian Niutitang Formation in South China should be focused on the shale development area where the shale is characterized by moderate thermal evolution degree (2.0% < Ro < 3.0%) and shallow buried depth, that is, the shale distribution area with paleo-uplift or paleo-buried hill. Keywords: Organic pores, TOC, Thermal evolution degree, Shale, Niutitang formation, Lower cambrian, South China